2017
DOI: 10.1002/ppul.23918
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and anatomical dead space in mechanically ventilated newborn infants

Abstract: wileyonlinelibrary.com/journal/ppul

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 25 publications
2
22
1
Order By: Relevance
“…Few studies have reported neonate V d,alv values [7,11]. Dassios et al reported a median V d,alv of 0.3 ml/kg in prematurely born infants with a median weight of 1.18 kg, and 0.1 ml/kg for infants with a median weight of 3.3 kg; we report a higher mean V d,alv 0.6-1.0 ml/kg [7].…”
Section: Discussioncontrasting
confidence: 44%
“…Few studies have reported neonate V d,alv values [7,11]. Dassios et al reported a median V d,alv of 0.3 ml/kg in prematurely born infants with a median weight of 1.18 kg, and 0.1 ml/kg for infants with a median weight of 3.3 kg; we report a higher mean V d,alv 0.6-1.0 ml/kg [7].…”
Section: Discussioncontrasting
confidence: 44%
“…When compared with term-born infants, premature infants have an increased anatomic dead space, so P ETCO 2 is very likely to be lower than arterial CO 2 . 22 We studied the range of CPAP levels in each infant, so factors like the increased dead space and relatively increased ventilation efficiency index did not influence the validity of our conclusions.…”
Section: Discussionmentioning
confidence: 94%
“…Dassios et al, compared physiologic and anatomic dead space in a retrospective analysis of mechanically ventilated newborns just prior to extubation. 11 Since the study subjects had largely recovered, their measurements could imply that the premature patients with higher dead space had already sustained some stunting of alveolar development, or that tracheobronchial enlargement, a known complication of prolonged ventilation in premature newborns, was contributing. This is additional evidence that avoiding positive pressure is desirable if not achievable in this population.…”
Section: Preventing Bpd: Practicementioning
confidence: 99%